Asuhan Komprehensif pada Ibu Hamil Preeklamsia di Puskesmas Jumo Kabupaten Temanggung - Rini Setyani; Ida Sofiyanti (Universitas Ngudi Waluyo, 2025)
Pregnancy is defined as the natural process of fertilization or the union of spermatozoa and ovum, followed by nidation or implantation. Pregnancy and childbirth are normal processes, but there is still a 10% chance of someone experiencing complications during pregnancy and childbirth. Preeclampsia is one of the